Recurrent pneumonia in a patient with bone deformity: a case report of ricketts - Zapata-Chica, Carlos Andrés (2020)
Ricketts is a rare bone disease associated with low serum levels of calcium and phosphate. Most of the cases occur as a consequence of nutritional deficits, but genetic mutations or acquired metabolic defects may account for it. Clinical presentation is heterogenous depending on age at presentation, manifesting as widening and retardation of mineralization of the growing bone plate. We present the case of a 11 month of age child with a history of recurrent pneumonia presenting with generalized muscle hypotonia, deformed chest and bowed extremities with hypocalcemia and hypophosphatemia, elevated levels of alkaline phosphatase and parathyroid hormone, high levels of 25-hidroxy-vitamine D3 and very low levels of 1,25-dihidroxy-vitamine D3 suggesting the diagnosis of severe vitamin D type 1A rickets, a rare form of this disease.